Pengaruh Aglomerasi, Angkatan Kerja Dan Human Capital Investment Terhadap Pertumbuhan Ekonomi Kabupaten Simalungun - Rukmana, Nadia Mayang; Lubis, Fauzi Arif; Atika, Atika (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine the effect of agglomeration, labor force and Human Capital Investment on economic growth Simalungun. This study uses a quantitative approach. Simalungun is one of the districts in North Sumatra province. industrial concentration that creates consumption patterns that affect the economic development of the surrounding area, then the labor force that can encourage economic growth in increasing production factors, the last human capital investment/ HDI is an area that has adequate human capital in terms of knowledge, health and skills that can encourage economic growth. This research data obtained from secondary data with data collection techniques used are literature and documentation studies. The analysis technique used is multiple linear regression test using SPSS analysis tools. The results of this study show that simultaneously agglomeration (X1), labor force (X2), and Human Capital Investment (X3) have a positive and significant effect on economic growth (Y). Partially agglomeration has a positive and significant effect on economic growth with a t-count value of 5.432 and a significant value of 0.003 smaller than the specified significant value. The labor force has a negative and significant effect on economic growth with a calculated t-value of -3.711 and a significance value of 0.014 less than the specified significant value. Human Capital Investment has a positive and significant effect on economic growth, with a calculated t value of 21.643 and a significance value of 0.000 smaller than the specified significance value.